Synthesis And Characterization of Polymeric V2O5/AIO(OH) With Nanopores On Alumina Support - Ahmad, A. L.; Abd Shukor, S. R.; Leo, C. P.; Pramanik, P. (2005)
Polymeric vanadium pentixide gel was formed via the reaction of V2O5 powder with hydrogen peroxide. The polymeric vanadium pentoxide gel was then dispersed in alumina gel. Different vanadium loading composites were coated on alumina support and calcined at 500C for 1 hr. These composite layers were characterized using EDX, FT-IR, XRD, SEM, TGA and Autosorb. It was found that the lamellar structure of polymerized vanadium pentoxide was retained in the inorganic matrix. Crystalline alumina in gamma phase was formed after calcinations. However, crystalline V2O5 was not found in the composite layer and it was possibly due to low calcination temperature. Alumina top layer with 21.81 wt% of V2O5 gel showed smaller pore diameter (5.483.nm) and improved BET surface area (380.4m2/g).